Development and Validation of UV-Visible Spectrophotometric Method for Estimation of Levodopa - Kapde Ghrushneshwar; Wakte Pravin; Bhusari Sachin (Asian Journal of Pharmaceutical Research and Development, 2025)
Aim: The aim of the proposed study was to development and validation of simple, accurate, precise yet economical UV-Visible spectrophotometric method for the quantitative estimation of Levodopa. Methods: A UV–Visible spectrophotometric method was developed using a co-solvent system consisting of 20% methanol and 80% 0.01M potassium hydrogen phosphate buffer (K₂HPO₄). Levodopa solution was scanned over the entire UV-visible range to determine its wave length of maximum absorbance. The method was validated in accordance with the ICH Q2(R1) guidelines which involves various parameters viz. linearity, accuracy, precision, robustness, ruggedness, limit of detection (LOD), and limit of quantitation (LOQ). Results: The wavelength of maximum absorbance (λmax) for Levodopa was observed at 283 nm using a co-solvent system composed of 20% methanol and 80% 0.01M potassium phosphate buffer (K₂HPO₄).The developed UV–Visible spectrophotometric method demonstrated excellent linearity across the concentration range of 5 to 60μg/mL, with a correlation coefficient (r²) of 0.999. The intra-day accuracy in terms of % Differencewas in the range of −7.88% to +4.46% and Inter day accuracy was in the range of −7.60% to +2.42%. The precision values(% RSD) were found to be below 3% for both intra- and inter-day studies. Robustness and ruggedness studies confirmed the method’s reliability under deliberate variations in analytical conditions with %RSD values below 3%. The limit of detection (LOD) and limit of quantitation (LOQ) were determined to be 0.9189μg/mL and 2.7884μg/mL, respectively, ensuring adequate sensitivity for routine quality control analysis. Conclusion: A simple, accurate, precise and cost-effective UV-visible spectrophotometric method was successfully developed for the estimation of Levodopa. The method was developed using an economical percentage of the organic phase in co-solvent system. The validated UV-Visible method was found to be efficient for the estimation of Levodopa in the commercial samples. Considering the advantages, said developed method can be used for the routine analysis of Levodopa.